Field Study on Duck Rearing Practices and the Economic and Social Factors Influencing the Acceptance of Its Products in Various Areas of Al- jabal alakhdar (Comprehensive Journal of Science, 2025)
This study aimed to explore duck farming practices in Al- jabal alakhdar , focusing on the characteristics of the farmers, their farming systems, feeding practices, diseases, and factors affecting productivity. The research employed a field survey methodology and a questionnaire consisting of 34 questions, with 32 duck farmers .The results showed that most farmers were male and all of the same nationality, with an average to high level of education and an average income. The majority relied on open-range farming, with a tendency towards multi-production (eggs and meat). The average number of ducks was higher in open-range farming. The most common duck breeds were mixed breeds (various types) and Iraqi ducks. The most common percentage of males in flocks was 20%. Open-range feeding was varied, while some farmers used closed-range feeding with supplements. Open-range farming tended to result in a larger number of ducks with less variation. The distribution of potential diseases was similar between the two farming methods (closed and open), and the chi-square test showed no statistically significant difference.Although duck farming is not widespread in the region, the presence of a group of farmers represents a good opportunity to develop this agricultural activity and improve local production. It is recommended to encourage farmers to adopt modern breeding practices and improve feeding and healthcare systems for ducks, along with organizing training and guidance programs to increase production efficiency and reduce health risks.
Keywords: Bat Rearing, Nutrition, Production, Diseases, Green Mountain, Open Rearing, Mixed Duck